ENCICLOPEDIA ITALIANA : DI SCIENZE, LETTERE ED ARTI - Gentile, Giovanni (dirección) (1929)
CONTENIDO: V. 1 A-AGRI. -- V. 2 AGRO-AMMI. -- V. 3 AMMO-ARBI. -- V. 4 ARBO-ASSE. -- V. 5 ASSI-BALS. -- V. 6 BALTA BIK. -- V. 7 BIL-BUB. -- V. 8 BUC-CARD. -- V. 9 CARE-CHIA. -- V. 10 CHIB-COMPE. -- V. 11 COMPI-CROCC. -- V. 12 CROCE-DIR.-- V. 13 DIS-ENN. -- V. 14 ENO-FEO. -- V. 15 FER-FRANCI. -- V. 16 FRANCK-GIAN. -- V. 17 GIAP-GS. -- V. 18 GU-INDE. --V. 19 INDI-ITA. -- V. 20 ITE-LET. -- V. 21 LEU-MALB. -- V.22 MALC-MESSIC. -- V. 23 MESSIE-MS. -- V. 24 MU-NOVE. -- V. 25 NOUG-PALEN. -- V. 26 PALEOPETE. -- V. 27 PETH-PORTH. -- V. 28 PORTI-REG. -- V. 29 REH-ROMANI. -- V. 30 ROMANIA-SCAP. -- V. 31 SCAR-SOC. -- V. 32 SOD-SUO. -- V. 33 SUP-TOPI.-- V. 34 TOPO-VED. -- V. 35 VEG-ZYG. -- V. 36 APENDICE. --V. 37 INDICI